(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The tree-like, fractal structure of universal (including legal, law-governed) laws, norms and rules has been explored and justified. The physical example for the fractal structure (spruce, pine, etc.) shows a experimental technique for measuring their basic physical parameters: mass, density, volume, and the side surface area. It is proposed that norms, laws and rules have to have the short, compressed, concise, simple, clear, and simple-to-follow in contents. This follows from the fractal theory of building the human society. And from the intelligent construction of the algorithm of human life and activity. Positive aspects of the Hadith presentation style were noted.